Metastatic Extrapulmonary Small Cell Carcinoma to the Cerebellopontine Angle: A Case Report and Review of the Literature. (25th February 2015) - Theodros, Debebe; Goodwin, C. Rory; Crane, Genevieve M.; Liauw, Jason; Kleinberg, Lawrence; Lim, Michael
Abstract : Extrapulmonary small cell carcinomas (EPSCC) are rare malignancies with poor patient prognoses. We present the case of a 63-year-old male who underwent surgical resection of a poorly differentiated small cell carcinoma, likely from a small intestinal primary tumor that metastasized to the cerebellopontine angle (CPA). A 63-year-old male presented with mild left facial paralysis, hearing loss, and balance instability. MRI revealed a 15 mm mass in the left CPA involving the internal auditory canal consistent with a vestibular schwannoma. Preoperative MRI eight weeks later demonstrated marked enlargement to 35 mm. The patient underwent a suboccipital craniectomy and the mass was grossly different visually and in consistency from a standard vestibular schwannoma. The final pathology revealed a poorly differentiated small cell carcinoma. Postoperative PET scan identified avid uptake in the small intestine suggestive of either a small intestinal primary tumor or additional metastatic disease. The patient underwent whole brain radiation therapy and chemotherapy and at last follow-up demonstrated improvement in his symptoms. Surgical resection and radiotherapy are potential treatment options to improve survival in patients diagnosed with NET brain metastases. We present the first documented case of skull base metastasis of a poorly differentiated small cell carcinoma involving the CPA.